The Reformation Of Nguyen Truong To In The History Of Southeast Asia In The 19th Century (Journal of Namibian Studies : History Politics Culture, 2023)
Southeast Asia, including Vietnam in the nineteenth century, is a volatile area. Countries in the region have been invaded by colonial countries. In that period, in some countries in the region appeared the idea of reform of the country in which the reform of Nguyen Truong To the idea of historical significance is not only for Vietnam but also in the region of southeast Asia. With nearly 60 proposals, his country's innovative ideas are a bright spot in the process of the history of modern Southeast Asia. This research is based on surveys of archived documents referring to Nguyen Truong To's reform proposals still in Vietnam. This study uses documentary and logical methods to clarify the research problem. The highest goal of the research is to point out the advances that Nguyen Truong To proposed to reform Vietnam at the end of the 19th century.